Systematic Literature Review: The Role of Higher Education Institutions in Driving Economic Growth through Innovation and Human Resources - Nurfitriana Nurfitriana; Immarotul Ummah; M. Ridho Saputra; Tedi Purnama; Relasari Relasari (UNIVED Press, 2026)
This study aims to analyze the role of higher education in promoting economic growth through innovation and human capital development using a Systematic Literature Review (SLR) approach. The study reviews 30 open-access articles published between 2016 and 2026, selected based on their relevance to higher education, innovation, and economic growth. The findings show that higher education plays a strategic role in supporting economic growth both directly and indirectly. Direct contributions occur through the enhancement of human capital quality, while indirect effects are mediated by innovation, technological development, and cross-sector collaboration. The results also indicate that the quality of education, particularly at advanced levels, has a greater impact than the quantity of graduates. However, challenges such as regional disparities, limited infrastructure, and weak institutional collaboration remain significant barriers. Therefore, strengthening education quality, innovation capacity, and policy support is essential to achieve sustainable economic growth.